2023
DOI: 10.1021/acs.langmuir.3c02464
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of NO2, SO2, H2S, and NH3 on Os-Doped WSe2 Monolayers: A First-Principles Study

Long Lin,
Xinchun Li,
Chaowen Xue
et al.

Abstract: In this study, DFT calculations are used to analyze the adsorption of industrial waste gases (NO2, SO2, H2S, and NH3) on WSe2 monolayers. The adsorption energy, energy band, density of states, charge transfer, and recovery time of the adsorption structures between the target gas molecules and the Os-doped WSe2 are studied. Compared with pure WSe2 monolayer, Os surface bonding doping WSe2 (Os-modified WSe2) and Os doping with Se vacancy of WSe2 (Os-embedded WSe2) exhibit improved gas molecule adsorption ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…All the structural relaxation and electronic structure calculations are performed in VASP software . The Perdew–Burke–Ernzerhof (PBE) functional and the generalized approximation gradient (GGA) are used to calculate the exchange-related energy . The interaction between ions and electrons is treated using the Projector Augmented Plane Wave (PAW) method .…”
Section: Methodsmentioning
confidence: 99%
“…All the structural relaxation and electronic structure calculations are performed in VASP software . The Perdew–Burke–Ernzerhof (PBE) functional and the generalized approximation gradient (GGA) are used to calculate the exchange-related energy . The interaction between ions and electrons is treated using the Projector Augmented Plane Wave (PAW) method .…”
Section: Methodsmentioning
confidence: 99%
“…As a common gas in industrial production, nitrogen dioxide (NO 2 ) can lead to grave respiratory problems, including inflammation of the trachea and accumulation of fluid in the lungs. Moreover, recent investigations have shown that NO 2 is closely related to the prevention and transmission of COVID-19. , And it is also a significant account of environmental pollution such as summer smog, acid rain, and PM 2.5, which poses a major endangerment to mankind’s health and the safety of other life on the earth. , According to the OSHA regulations, the maximum concentration of short-term exposure to NO 2 is 5 ppm in industry. Long-term exposure to high concentrations of NO 2 can lead to poor breathing, lung disease, and even death. , Additionally, nitric oxide (NO) is a major contributor to air pollution and can have an unfavorable influence on mankind’s health.…”
Section: Introductionmentioning
confidence: 99%